On the processing and characterization of smart composite reinforcement - Kalamkarov, Alexander L.; Fitzgerald, Stephen B.; Georgiades, Tasos (My University, 1998)
The issues of processing and characterization of pultruded smart composite reinforcements with the embedded fiber optic sensors are discussed. These fiber reinforced polymer (FRP) reinforcements incorporate the optical fiber sensors to provide a strain monitoring of structures. The required modification of the pultrusion processing technology to allow for the incorporation of fiber optic sensors is developed. Fabry Perot and Bragg Grating optical strain sensors were chosen due to their small size and excellent sensitivity. The small diameter of the sensor and optical fiber allow them to be embedded without adversely affecting the strength of the composite. Two types of reinforcement with vinylester resin were used to produce the experimental 9.5 mm diameter rods. The reinforcements were carbon and E-glass fibers. In order to fully characterize the pultrusion process, it was decided to subject the strain sensors separately to each of the variables pertinent to the pultrusion process. Thus, sensors were used to monitor strain caused by compaction pressure in the die, compaction pressure plus standard temperature profile, and finally compaction pressure plus temperature plus resin cure (complete pultrusion process). A strain profile was recorded for each experiment as the sensor travelled through the pultrusion die, and for the cool-down period after the sensor had exited the die.
Keywords: Optical fiber detectors; Strains and stresses; Pultrusion